Strategic Aspects of Professional Position Development: Implications for Adjustment from Administrative to Professional Positions in Indonesia - Sumanti, Rati; Yunita, Ervina; Sinurat, Henri Prianto (Jurnal Borneo Administrator, 2021)
The mandate of government policy is to flatten bureaucracy structure through transferring administrative positions to professional ones. Such policy has caused many issues. Thus, it is necessary to develop professional positions. This research analyses three strategic aspects of professional position development that include legal, technical, and welfare aspects using a systematic literature review method. It shows that the legal aspect requires certain policies to accelerate the implementation of flat bureaucracy and problem-solving in organizational structure as well as in personnel management. The government's commitment is required by the planning system related to the development of professional positions both at the central and regional levels. In the technical aspect, the analysis shows competency development become mandatory for agencies to solve the competency gap between administrative positions and professional positions. Then on the welfare aspect, there is an income gap between administrative positions and several professional positions. The government has to make a regulation about allowance to resolve the income gap.